Electrochemical determination of clenbuterol with differential pulse voltammetry technique at carbon dots-based rice straw-modified electrode - Do, Mai Nguyen; Nguyen, Van Hop; Nguyen, Le My Linh; Tran, Thanh Tam Toan (Hue University Journal of Science: Natural Science, 2024)
In the present study, the carbon dots (CD) were extracted from rice straw (RS) and denoted as RSCD. The obtained material was examined by using techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), and nitrogen adsorption/desorption isotherms. The RSCD material was employed as an electrode modifier to improve the effectiveness of an electrochemical sensor for determining clenbuterol (CLB). RSCD showed fabulous oxidation towards clenbuterol. The modest detection limit could confirm an LOD value of 0.094 µM within a linear range between 0.1 and 1.8 µM under suitable conditions and the proposed technique –– the differential pulse voltammetry (DPV). The developed sensor exhibited several benefits: simplicity, low cost, effortless generation, fabulous selectivity, and good reproducibility.